KONTRIBUSI TEAMWORK DALAM MENINGKATKAN EFISIENSI OPERASIONAL DAN PROFITABILITAS CABANG BMT - Marianingsih, Ita; Hidayat, Andi Rahmad; Kazimah3 (SEKOLAH TINGGI ILMU SYARIAH ABU ZAIRI BONDOWOSO, 2025)
This study aims to analyze the contribution of teamwork in improving the operational efficiency and protectability of BMT branches. This study uses a qualitative descriptive technique, which is a process of observation as well as literature studies cited from relevant sources to gain in-depth insight into the role of teamwork in BMT branches. Mention relevant literature sources to provide a theoretical and contextual basis regarding teamwork, operational efficiency, and profitability. This literature will include relevant theories, models, and previous findings. The purpose of this review is to provide an alternative for workers or employees in improving operational efficiency and profitability of branches while maintaining teamwork as well as assessing how teamwork contributes to improving operational efficiency and profitability. With good teamwork, coordination between team members becomes more effective. This minimizes overlapping tasks and ensures that each team member clearly understands their roles and responsibilities. Good cooperation creates synergy, where the combined efforts of individuals produce greater results than if they worked separately. This helps the team to achieve common goals more efficiently. With this structure and approach, the research is expected to provide in-depth insights and practical recommendations.